SIMULATION OF REDUCTION ORDER MODEL LTNEAR PARAMETER VARYING (LPV) SYSTEMS USING MATLAB SOFTWARE - Rahma Zuhra (Proceedings of ICMSA, 2005)
The use of optimal control techniques on high-order systems producehigh-order controller. Therefore, an approximation from high-ordersystem to low-order system is needed. The approximation is known asreduction model. In this paper we study one of reduction model ofLinear Parameter Varying (LPV) i.e. method balanced truncation. Theprocedure of this method can be stated as follows:First, the quadraticstable (Q-stable) is shown for given a high-order of LPV. Second, thestate space realization ofthe high-order LPV plant is transformed to thebalanced realization. Third, the balanced realizations are truncated toobtain the reduced-order plant. Fourth, the reduced-order plant isshown similar properties with the high-order plant. Finally, thesimulation is carried out for a missile autopilot by using LMI Controltoolbox and Robust Control toolbox in MATLAB software. From thesimulation results we obtain that the reduction system has similarproperties with the high-order system, i.e. Q-stable and balanced.Keywords: LPV system, Q-stable, LPV Balanced Truncation, LMIControl toolbox and Robust Control toolbox.